THE AGRIBUSINESS START-UP OF SHALLOT HIDROPONIC: OPPORTUNITIES AND CHALLANGING CASE SATUDY ON SIE-FARM JEMBER - Mohammad Rondhi; Subhan Arief Budiman; Rokhani Rokhani; Ali Badrudin; Fendi Setyawan (UPT Penerbitan Universitas Jember, 2022)
Red onions (shallots) are an important commodity in the Indonesian economy, both in terms of contribution to national income and as a commodity for controlling the price of goods. Red onion farming is usually cultivated conventionally in paddy fields requiring intensive labor. Recently, several youths in a village in Jember, East Java, have been cultivating red onion hydroponically for the last three years. The business has good prospects but has problems in its development. This study aims to map the strengths and obstacles faced and to determine the right strategy. The analytical method used is descriptive with a field force analysis approach. The analysis results show that the strength factors possessed include experience, both farming experience and market experience, product diversification capabilities, and support in the form of networking with related agencies. While the inhibiting variables include limited market access, limited access to funding, and limited skilled resources. Based on the FFA analysis, it is known that the most important weight is the increase in cultivation skills and the ability to diversify products. The results of this study recommend that startup actors need to be vigilant in undergoing the initial phase of business implementation, which has many obstacles and needs to have a strategy by increasing post-harvest processing skills. Keywords: red onion agribusiness, field force analysis,